Perancangan Jaringan LTE FDD (Frequency Division Duplex) Dengan Frekuensi 1800 MHZ Di Kabupaten Indragiri Hulu - Syahputra, Adi; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Long Term Evolution Advanced (LTE) is a communication standard of access based on GSM / EDGE and UMTS / HSPA networks. One of the advantages of LTE is that it offers high data transfer speeds if compared to previous Network Technology. Nowadays, Network Technology entered the Industrial 4.0 where as the system covers physical cyber, internet for everything, cloud computing and cognitive computing all things cause all activities are influenced by networks. However, the allocation of LTE development in Indonesia is not yet widespread, especially in small areas such as Indragiri Hulu Regency. The LTE network in Indragiri Hulu Regency is still categorized as not optimal based on network analysis using a Network Tracking Application, was called Nperf. Therefore this paper aims to design an LTE FDD network in Indragiri Hulu District using Software Radio Planning Atoll with frequency of 1800 MHz. This study uses two scenarios, namely with a bandwidth of 5 MHz and 10 MHz. Then the scenario will be analyzed by comparing the optimal data output. The parameter test results show that the Coverage by Signal Level in the 10 MHz scenario is superior at 99.32% with the signal value > -80 dBm it is categorized very good on the Shapefile (SHP) produce in the 5 MHz scenario the result value is 98.84% on the Shapefile (SHP) map caused by the parameters used on the otherside different wider radius value for each cell. It causes interference. The comparison of Monte Carlo simulation between 5 MHz and 10 MHz bandwidth at 1800 MHz frequency that the 10 MHz bandwidth of users connected to the network is more effective with a value of 96.325% than the 5 MHz bandwidth of 94.95%. It can be concluded that the scenario of using 10 MHz bandwidth is more optimal used in the construction of LTE with a frequency of 1800 MHz.Keyword : LTE, Software Radio Planning Atoll, Signal Level, Bandwidth, Monte Carlo Method.